The prophecy of the Messenger of God Muhammad (may God bless him and his family and grant them peace) About the people of Morocco and their support for Islam (Journal of the College of Basic Education, 2024)
God Almighty rewarded His Messenger Muhammad bin Abdullah (may God’s prayers and peace be upon him and his family) with miracles and prophecies, throughout the path of his call to the Islamic religion. This was for many reasons, the most important of which was to demonstrate the sincerity of his call, and to discourage his opponents and those who denied his message to the infirm and deficient and their inability to carry out what he brought. The Messenger of God (may God bless him and his family and grant them peace), and the miracle that the Messenger (may God bless him and his family and grant them peace) performs was during the event - that is, a moment and at the same time in challenging the unbelievers and polytheists against him (may God bless him and his family and grant them peace). The second is the prophecy that he (may God’s prayers and peace be upon him and his family) would inform them of future events that would happen after his death, and it was not limited to his death only, but for the following centuries until the present day. Among his prophecies (may God’s prayers and peace be upon him and his family) was the entry of the people of the Arab Maghreb to Islam, and the improvement of their Islam. So that they can support him and spread his teachings in the northern regions, especially since the Arab Maghreb enjoys an important geographical location as a link to the European continent from the north.